Avaliação de pneus para carretas transbordo em tanques de solo - Monteiro, Leonardo de Almeida [UNESP]; Masiero, Fabrício Campos [UNESP]; Lanças, Kleber Pereira [UNESP]; Guerra, Saulo Philipe Sebastião [UNESP]; Jesus, Marcella Guerreiro de [UNESP] (My University, 2010)
The constructive type of the tire and pressure of used inflation results in different values in the increment of the compacting of the due soil the different weight distributions in relation to area of contact tire-soil. It was studied in this work: the contact areas, the total deformations and the compacting caused in the soil of two types of tires of sugarcane (diagonal and radial) change. The relative results to the contact areas showed larger values for the radial tire. The radial Tire presented larger deformation in the smallest inflation pressures, the diagonal tire behaved in an inverse way.

O tipo construtivo e a pressão de inflação do pneu resultam em diferentes valores no incremento da compactação do solo devido às diferentes distribuições de peso em relação à área de contato pneu-solo. Estudouse as áreas de contato, as deformações totais e a compactação causada no solo com dois tipos de pneus (diagonal e radial) utilizados em carretas transbordo de cana-de-açúcar. Os resultados relativos às áreas de contato mostraram maiores valores para o pneu radial. O pneu radial apresentou maior deformação nas menores pressões de inflação, o pneu diagonal se comportou de maneira inversa.
Evaluation of tires carretas landing in tank soil
Keywords: Compacting of the soil; Deformation of the turned tires; Inflation pressure; Compactação do solo; Deformação de rodados pneumáticos; Pressão de inflação